IC 9059 Precious Metals Recovery From Low-Grade Resources - Proceedings: Bureau Of Mines Open Industry Briefing Session At The National Western Mining Conference, Denver, CO, February 12, 1986 (The National Institute for Occupational Safety and Health (NIOSH), 1986)
This information circular describes research the Bureau of fines has conducted to improve technology for recovering precious metals from low-grade resources. Many of the reported findings are recent, and some of the work described is ongoing. Topics discussed include cyanidation of carbonaceous gold ores to enhance gold recovery, a new method for precipitating mercury during cyanide leaching of gold ores, a staged heap leaching process to generate suitable solutions for direct electrowinning of gold, the use of anion-exchange resins to recover gold from cyanide solutions, and precious metals recovery from electronic scrap.